Insight into the Effects of the Anchoring Groups on the Photovoltaic Performance of Unsymmetrical Phthalocyanine Based Dye-Sensitized Solar Cells - Cardenas-Jiron, G; Zambrano-Angulo, M (Royal Society of Chemistry, 2021)
Push-pull zinc phthalocyanine dyes bearing hexylsulfanyl moieties as electron donors and carboxyethynyl as mono- or di-anchoring groups have been designed, synthesized and tested as sensitizers in dye-sensitized solar cells (DSSCs). The effects of the anchoring groups on the optical, electrochemical and photovoltaic properties were investigated. The incorporation of a carboxyethynyl group inGT23has a considerable effect on preventing dye aggregation due to its relatively non-planar structure. The mono-anchoring dye bearing a phenyl carboxyethynyl group,GT5, has a higher molar extinction coefficient and sufficient charge injection into the TiO2conduction band. Therefore,GT5achieved at least 90% higher power conversion efficiency than the di-anchoring dyes (GT31andGT32). Time-dependent density functional theory (PBE0/6-31G(d,p)) was also used to calculate the electronic absorption spectra, which predicted very well the measured UV-Vis with an error of up to 0.11 eV for the Q bands and 0.3 eV for the B bands. The longest charge transfer bands are obtained in the visible light region and they correspond to a transfer phthalocyanine core → substituent with a carboxyethynyl group where the absorptions ofGT32(465 nm) andGT31(461 nm) are red-shifted compared toGT23(429 nm) andGT5(441 nm). The interaction energy between the phthalocyanine and a cluster of anatase-TiO2(H4Ti40O82) was calculated using density functional theory. For all phthalocyanines, the interaction favored is monodentate and corresponds to -O(OH)⋯Ti(TiO2), where the stronger interaction occurs forGT32(−2.11 eV) andGT31(−2.25 eV). This study presents the molecular combination of the anchoring groups in zinc phthalocyanine sensitizers, which is one of the effective strategies for improving the performance of DSSCs. © The Royal Society of Chemistry 2021.